As políticas públicas fiscais do FDI no Ceará e o desenvolvimento econômico-social: uma análise das políticas do FDI entre 2015-2023 - Teixeira, Rosana Lima (2024)
The objective of this study is to analyze the legislation of the Industrial Development Fund (FDI) of the state of Ceará, from its creation, State Law no. 10.367/1979, and the socioeconomic contributions brought about by the implementation of the referred fund. The research provides a historical outline that presents the origin of the industry in the state until the period of the creation of the law and the reasons for its implementation, in addition to referencing several parameters in the developmental identification of the sector in the state of Ceará. Discussions are established about the FDI, whether it is a fiscal public policy or not, bringing to the fore the characteristics of public policies, from a doctrinal perspective and their correlation with government policies. Based on this analysis, the methodology to be used in the research is presented, in which a doctrinal, therefore qualitative, research is chosen, as well as quantitative elements provided by the state of Ceará, through official data, between the years 2015 and 2023, which show the importance of FDI in industrial development, bringing correlations with temporal elements that had effects at the time analyzed, such as, for example, the year 2020, due to Covid-19.